Economic report of the President : transmitted to the Congress January 1979 - United States President Jimmy Carter; Council of Economic Advisers (U.S.). (Washington : United States Government Printing Office, 1979)
This volume deals with the problem of inflation and policies to control it. It also focused on the economic outlook, world economy & managing interdependence as well as the changing environment of world trade.
rpm 10/05/2017
Loans
Keywords: United States -- Economic policy; United States -- Economic conditions -- 1945-; Economic history; Economic policy; United States